The Effect of Cooperative Supervision Effectiveness on Cooperative Accountability in Bima City - Luthfiyyah Sulthanah; Adhitya Bayu Suryantara (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The targets of cooperative accountability include achieving accountable cooperatives, increasing trust, and enhancing reputation. The purpose of this study is to examine whether there is a positive influence of governance on organizational and management aspects; risk profile, financial performance, and capitalization on business and service aspects for members and finance aspects; and health assessment on the implementation aspects of accountability dimensions. A total of 37 respondents constituted the sample for this research, which involved active cooperatives in the city of Bima. This study utilized SPSS version 23 and incorporated both primary and secondary data. Primary data was collected through questionnaires as the data collection method, while secondary data was sourced from LHPKK reports provided by the DisKoperindag. Research findings revealed that capitalization assessment had a positive effect on business and service aspects for members, as well as on finance aspects. However, governance assessment did not impact organizational and management aspects, nor did risk profile assessment and financial performance impact business and service aspects for members and financial aspects. The health assessment showed no influence on the execution of accountability dimensions. The implication of this study is the effectiveness of cooperative supervision in ensuring that cooperatives operate transparently and responsibly, thereby enhancing cooperative accountability.